PELATIHAN PENYIMPANAN DIGITAL SISWA PADA SMA DAN SMK GALA JUARA BEKASI - Adi Muhajirin; Dani Yusuf; Dwipa Handayani; Mukhlis Mukhlis; Tyastuti Sri Lestari (Universitas Islam kalimantan MAB, 2018)
The presence of the internet in everyday life has changed the way modern people live. The field of administrative work is the most changing field. One of the changes in the way the administration works is with the concept of paperless office or paperless office concept. Schools as a means of education can take advantage of the concept of paperless office to reduce operational costs and improve the quality of information services valid student data/i. The object of this devotion, addressed to SMA and SMK gala champions who do not have digital-based storage. providing training to senior high school and vocational high school staffs in having valid data and reducing paper usage. The data were collected by library study and observation. SMA and SMK Gala Juara experienced obstacles in the recording of complete student data due to lack of human resources who have the ability in the field of IT and lack of time allocation in preparing reports. The purpose of this dedication is to help SMA and SMK Gala Juara to minimize misunderstandings on student data recording digitally and integrated.Keywords: Paperless Office, Green ICT, Integrated